¿Es necesario la evaluación del riesgo de sesgo en revisiones sistemáticas de series o reportes de caso? - Pichardo-Rodriguez, Rafael; Saavedra-Velasco, Marcos; Gonzales-Rospigliosi, Cristhian; Cordova-Cueva, Liz; Munayco-Guillen, Fernando (Revista Médica Herediana, 2024)